DIGITAL TRANSFORMATION OF THE GLOBAL FINANCIAL BUSINESS - PRYKHODKO, Borys; PAVLOVSKYI, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines the current issues of digitalization of the global financial business. The author analyses digital transformations in public, corporate, and international finance. It is confirmed that along with scaling and outpacing development, territorial and segmental integration and conversion, and deregulation with the transition to turbulence, the digitalization of the global financial market has become increasingly revolutionary in the last decade. The article identifies the peculiarities of digitalizing financial relations, especially international ones, and their impact on financial services’ range, scale, dynamics, and efficiency, the interaction of economic agents, and the system and methods of international cashless payments. The identification of digital technologies based on big data, ICT, broadband Internet, and wireless mobility is generalized. The article highlights the gradual evolution of digital technologies in the modern technological paradigm, focusing on blockchain technology. Its advantages related to the cost of transactions, their speed, security, and financial inclusion are summarised. The types of digital business models are identified and characterized. A logical and structural scheme for the formation of digital models of global financial business is proposed. It is argued that hard and soft digital infrastructure provides access to digital technologies, and the corporate strategy of digital transformation of financial institutions should consider the growing competitive pressure of attractive IT platforms for customers. Digital business models should be based on digitizing key business processes and management and forming a corporate digital culture. Attention is focused on the growing risks of global digitalization when hacker attacks take the form of organized cybercrime and state terrorism, which necessitates the creation of corporate cybersecurity systems integrated into the national security system.